2011
DOI: 10.1016/j.neuroscience.2010.10.046
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic transmission modulates ethanol excitation of ventral tegmental area dopamine neurons

Abstract: Activation of the dopaminergic (DA) neurons of the ventral tegmental area (VTA) by ethanol has been implicated in its rewarding and reinforcing effects. We previously demonstrated that ethanol enhances GABA release onto VTA-DA neurons via activation of 5-HT 2C receptors and subsequent release of calcium from intracellular stores. Here we demonstrate that excitation of VTA-DA neurons by ethanol is limited by an ethanol-enhancement in GABA release.In this study, we performed whole-cell voltage clamp recordings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 47 publications
7
50
0
Order By: Relevance
“…Projections from the VTA extend to regions implicated in the rewarding potential of drugs of abuse, including the NAcc (Van Bockstaele and Pickel, 1995;Olson et al, 2005) and the PFC (Carr and Sesack, 2000). An activation of the caudal VTA dopaminergic neurons, which is mediated by a reduced GABAergic signaling (Theile et al, 2011), is one of the cellular bases for alcohol reinforcement (Brodie et al, 1999;Xiao et al, 2009). Several studies have demonstrated that as the GABAergic activity in rostral VTA increases, the dopaminergic activity decreases, resulting in a diminished experience of reward and reinforcement (Ikemoto et al, 1997;Ding et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Projections from the VTA extend to regions implicated in the rewarding potential of drugs of abuse, including the NAcc (Van Bockstaele and Pickel, 1995;Olson et al, 2005) and the PFC (Carr and Sesack, 2000). An activation of the caudal VTA dopaminergic neurons, which is mediated by a reduced GABAergic signaling (Theile et al, 2011), is one of the cellular bases for alcohol reinforcement (Brodie et al, 1999;Xiao et al, 2009). Several studies have demonstrated that as the GABAergic activity in rostral VTA increases, the dopaminergic activity decreases, resulting in a diminished experience of reward and reinforcement (Ikemoto et al, 1997;Ding et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the concentrations of ethanol required to induce these effects are typically higher than those consistent with social drinking (e.g., 25-50 mM, with a BAL of 80 mg/dL corresponding to 17.4 mM), suggesting that the action of ethanol on the mesolimbic DA pathway only partially mediates its reinforcing effects in vivo. The net effect of ethanol on the activity of VTA DA neurons results from the summation of excitatory and inhibitory influences, including (i) direct excitation (23,39); (ii) indirect excitation, via enhancement of glutamatergic input (40); (iii) disinhibition, via suppression of GABAergic input (41)(42)(43); and, in other instances, (iv) indirect inhibition, via enhancement of GABAergic transmission (44)(45)(46)(47). Continuous 2BC 6 days (Fig.…”
Section: Girk3 Deletion Prevents Ethanol-induced Release Of Da In Thementioning
confidence: 99%
“…GABA-A receptor antagonists, including picrotoxin (Theile et al, 2011) and bicuculline (Westerink et al, 1996), disinhibit VTA-DA release. Similarly, GABA-A receptor inverse agonist, FG7142, has been shown to activate VTA neurons (Murphy et al, 1996).…”
Section: Discussionmentioning
confidence: 99%